Evaluation of the pedagogical project of the chemical engineering course from IFNMG, Montes Claros campus (MG): a case study focused on curriculum analysis (Research, Society and Development, 2020)
This work aimed to carry out a critical analysis of the pedagogical project of the Chemical Engineering course (PPC) of the Federal Institute of Education, Science and Technology of the North of Minas Gerais - IFNMG, Montes Claros campus, version 3. Such assessment had as guiding principles the theoretical orientation of the document, the course approach in relation to the teaching-research-extension, the existence of interdisciplinarity and/or trandisciplinarity and how legislation is used for curricular reflection. The results show that the PPC of the referred course consists of a document that was built based on the precepts of the Federal Constitution, the Law of Directives and Bases of National Education (LDBEN), the National Curriculum References of the Bachelor and Licentiate Courses and the Guidelines National Curriculum of Engineering Courses. The curricular matrix is ​​divided into disciplines that constitute cores, as recommended by the legislation. Several particulars of the course are listed in order to work the contents interdisciplinarily. However, transversal themes are not yet part of the analyzed curriculum proposal.